The Influence of Work Discipline and Compensation on Work Effectiveness with Job Satisfaction as An Intervening Variable in Field Employees Authority Office Medan Region II Airport Authority - Muhammad Suliztyanto; Yohny Anwar; Chaerul Rizky (Lafadz Jaya Publisher, 2023)
This study aims to look at the Effect of Work Discipline and Compensation on Work Effectiveness with Job Satisfaction as an Intervening Variable. This research uses a quantitative associative research type, the research location is in the Field of Aviation Security, Medan Region II Airport Authority Office, the population of employees is 97 employees because the research took all samples. Then using saturated sample techniques, the research model is path analysis and research data collection using questionnaires and surveys. and significant to the effectiveness of this can be proven in the original Path Coefficients table sample 0.650 P values 0.000. Work Discipline has a positive and significant effect on Job Satisfaction, this can be proven in the original Path Coefficients table sample 0.881 P values 0.000. Job Satisfaction has a positive and significant effect on Job Satisfaction. This can be proven in the original Path Coefficients table sample 0.282 P values 0.002. Compensation has no significant positive effect on effectiveness, this can be proven in the original Path Coefficients table sample 0.060 P values 0.271. Compensation has no significant negative effect on job satisfaction. This can be proven in the original sample Path Coefficients table -0.063 P values 0.415. Job satisfaction can be an intervening variable on work discipline and work effectiveness. This can be proven in the original Path Coefficients table sample 0.249 P values 0.002. Job Satisfaction is not an intervening variable on Compensation and Work Effectiveness, this can be proven in the original sample Path Coefficients table -0.018 P values 0.443.